OPTIMALISASI PEMASARAN UMKM KERAJINAN PERAK KOTAGEDE DENGAN PELATIHAN DAN PENYEDIAAN PERANGKAT PENDUKUNG MARKETPLACE ONLINE - Kharisma, Rizqi Sukma; Yudaninggar, Kartika Sari; Wardhana, Raditya; Andiyansari, Popi; Maparoja, Wildansyah; Yancandra, Yogi Efani; Fitriyani, Ainar; Aprilian, Siva; Asmoro, Hapsari Puspa; Nusantara, Diajeng Putri (Jurnal Abdi Insani, 2024)
Silver crafts in Kotagede are one of the cultural heritages that have existed since the 17th century. Based on Yogyakarta City Regional Regulation Number 3 of 2015 concerning the Yogyakarta City Tourism Development Master Plan for 2015-2025, Kotagede has been designated a strategic regional tourism area. However, the number of silver craftsmen in Kotagede continues to decline due to competition with imported casting products, so many craftsmen have switched to other sectors. To increase sales, craftsmen need to expand marketing through online marketplaces. Therefore, this community service activity was held to help silver craftsmen learn to create posts and design sales strategies independently through online marketplaces. This activity was conducted through training on marketing strategies through online marketplaces, held at the Grand Rohan Hotel, Bantul, DIY, on July 27, 2024. The participants in this training were community service partners, namely Haseena Jewelry and ER Prapen, who focused on silver jewelry products. This training presented speakers from practitioners and lecturers at Amikom University Yogyakarta. In addition to training, this activity provides supporting devices for online marketplaces for partners, such as studio lighting, background stands, tripods, and wireless clip-on. These devices can be used by partners to support live online sales activities through the marketplace. From the evaluation results, the partners showed increased knowledge about online marketplaces.